MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI STRATEGI PROBLEM BASED (PBL) - Risna, Risna; Hatimah, Husnul; Khasanah, Uswatul; Alini, Alini; Abira, Abrar; Madjid, Tahmid (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
This study aims to activate the effectiveness of the problem-based learning model (PBL) in omproving learning motivation. The method used is a literature study by analyzing six relevant national journals. The results of the study indicate that PBL has appositive effect on improving student motivation. This is evidenced by the increase in learning achievement scores with high enthusiasm from students is undergoing the learning process. PBL not only increases learning motivation nut also student lerning outcomes because mastery of the material is more significant. PBL also succeeded in improving students cricital thinking and problem-solving skills as well as their ability to collaborate. It can be concluded thet PBL has proven to be an efeective approach to creating relevant, enjoyable, and applicable learning. This method is able to prepare students to face real-world problems by improving the overall quality of learning.